2008
DOI: 10.1002/cphc.200800617
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Spectrum of A–T DNA Unraveled by Quantum Mechanical Calculations in Solution on the (dA)2⋅(dT)2 Tetramer

Abstract: The absorption spectrum of A-T DNA is computed for the first time in aqueous solution by means of quantum mechanical calculations performed on realistic models, thereby accounting for both stacking and base pairing interactions and including solvent effects through the polarizable continuum model. The computed and experimental spectra are in close agreement. Our analysis allows the identification of all the electronic transitions hidden in the broad absorption spectrum of A-T DNA, thus determining their most r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
70
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 43 publications
7
70
2
Order By: Relevance
“…In these latter systems, the frontier orbitals can have a substantial overlap and the resulting electronic transitions delocalized over multiple bases. This is indeed the case of the lowest energy bright electronic transitions of stacked adenine nucleobases in polyAde single and double strands [133][134][135][136]. In this latter case, our studies in the field provide encouraging indications about the reliability of TD-DFT calculations when based on a suitable functional for the treatment of the excited states in p-stacked nucleobases.…”
Section: Dealing With Supramolecular Interactions: Optical Propertiessupporting
confidence: 57%
See 1 more Smart Citation
“…In these latter systems, the frontier orbitals can have a substantial overlap and the resulting electronic transitions delocalized over multiple bases. This is indeed the case of the lowest energy bright electronic transitions of stacked adenine nucleobases in polyAde single and double strands [133][134][135][136]. In this latter case, our studies in the field provide encouraging indications about the reliability of TD-DFT calculations when based on a suitable functional for the treatment of the excited states in p-stacked nucleobases.…”
Section: Dealing With Supramolecular Interactions: Optical Propertiessupporting
confidence: 57%
“…The optical properties of those systems are traditionally treated by semiempirical methods, where the interaction among the chromophores is included at a simplified level (e.g., by considering the dipolar/dipolar coupling between the excited-state transitions in the isolated chromophore). However, it is nowadays possible to attain a fully quantum mechanical description of the optical properties of complex supramolecular structures, as shown by the results obtained on DNA single and double strands [133][134][135][136].…”
Section: Dealing With Supramolecular Interactions: Optical Propertiesmentioning
confidence: 99%
“…photodynamical simulation | photostability | ultrafast photodeactivation | nonadiabatic interactions | ab initio multireference methods O wing to the importance of mutagenic and carcinogenic effects caused by UV radiation on DNA, the UV-induced photochemistry and photophysics of individual bases (1-7), base pairs (8)(9)(10), and nuclei acid strands (11)(12)(13) have been intensively studied. In each of these levels, it has been found that the genetic code may count on molecular mechanisms to get rid of the energy excess minimizing deleterious effects.…”
mentioning
confidence: 99%
“…Finally, theoretical calculations have described the existence of a variety of charge transfer states in DNA duplexes [12,27,28] , both intra-and inter-stand. It would not be surprising if such states, depending on orbital overlap, exhibit weak emission which is very sensitive to conformational disorder.…”
mentioning
confidence: 99%